2004
DOI: 10.1080/09595230410001645538
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the Safer Bars programme on physical aggression in bars: results of a randomized controlled trial

Abstract: The purpose of this study was to evaluate the effectiveness of Safer Bars, an intervention to reduce aggression in bars. A total of 734 pre - post-intervention observations were conducted by trained observers on Friday and Saturday nights between midnight and 2 a.m. in 18 large capacity ( > 300) Toronto bars and clubs assigned randomly to receive the intervention (69% participation rate of the 26 assigned) and 12 control bars. As part of the intervention, owners/managers completed the risk assessment workbook … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
120
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(127 citation statements)
references
References 25 publications
4
120
0
Order By: Relevance
“…As reported through participant-observation, service was rather slow at the bars of this particular barroom and patrons would often push one another to get access to the bar and order their beverage. This result complements previous findings (Graham et al 2004;, which reported that aggression at the serving bar is linked to poorly coordinated staff, which may result in frustrations and long queuing lines. Thus, situational prevention strategies at the serving bar might include ensuring a sufficient number of barmaids with better training in order to reduce aggression between patrons at this location.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As reported through participant-observation, service was rather slow at the bars of this particular barroom and patrons would often push one another to get access to the bar and order their beverage. This result complements previous findings (Graham et al 2004;, which reported that aggression at the serving bar is linked to poorly coordinated staff, which may result in frustrations and long queuing lines. Thus, situational prevention strategies at the serving bar might include ensuring a sufficient number of barmaids with better training in order to reduce aggression between patrons at this location.…”
Section: Discussionsupporting
confidence: 90%
“…In this vein, Homel et al (1992) argued that focusing intervention on barroom environmental factors is the most promising strategy to control or prevent aggression. Research has revealed that aggressive incidents are more frequent in bars with long queuing lines (Graham et al 2004), in crowded and small venues (Graham et al 2006), in bars where bouncers/security staff are too few, aggressive or poorly trained (Quigley et al 2003), and in premises where alcohol is served with little consideration for the client's level of intoxication (Buka and Birdthistle 1999;Gliksman et al 1993;Stockwell 2001). An efficient closing procedure is also crucial, as the number of people remaining after closing time is associated with the frequency and severity of aggressive acts (Graham et al 2006).…”
mentioning
confidence: 99%
“…12 Another review 8 identified a broader range of approaches to prevention encompassing RBS training (n = 6), enhancing the enforcement of licensing regulations (n = 2), multilevel interventions (n = 6), licensee accords (n = 2) and a risk-focused consultation (n = 1). The review highlighted that, of the available RCT evaluations that have been conducted in this area, only Graham et al 19 implemented a tailored intervention that was responsive to the idiosyncratic needs of premises, while Toomey et al 20 evaluated a risk-led intervention using quasi-experimental methods. Both of these studies concluded that premises-level interventions that are designed to offset risk factors in each premises are feasible and potentially effective.…”
Section: Interventions To Reduce Alcohol-related Violencementioning
confidence: 99%
“…12 Furthermore, the presence of empty glasses and other litter on tables may signal low levels of social order, and there is a relationship between untidy premises and disorder. 19,44,48,53,54 Promotions Stockwell et al 55 found that alcohol promotions were associated with intoxication but not associated with the risk of alcohol-related harm. More recently, however, studies suggest that promotions and becoming drunk are associated with police-recorded violence.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…Longer licensing hours would be expected to increase the risk of latenight violence and resultant homicide, and restricted licensing to reduce the opportunity for such risk [16]. The training of bar staff may have a positive impact, as there is evidence that interventions can influence whether staff escalate or de-escalate aggression in patrons [17]. The focus here is not upon national, global reductions in alcohol use, but in the circumstances in which it is sold and consumed.…”
mentioning
confidence: 99%